AJARAN ETIKA DALAM UPANISAD BAGI REMAJA HINDU DI ERA GLOBAL - Putu Prysthia Dirna (Jurnal Pendidikan Agama, 2021)
Upanisad is the essence of Vedas teachings which contain teachings on divinity, ritual, cosmos and ethics. Ethics is a teaching that teaches people to have good character. The teachings of ethics contained in this Upanishad can be used as a guide in living life in this era of globalization. At present, the era of globalization turns out to have a variety of impacts on life, one of which is social deviations that occur among the younger generation. This lack of understanding of ethical teachings is indeed a factor in the causes of declining morality. Some of the ethical teachings contained in this upanisad are about satya, tat twam asi, and also self-control. If these teachings are truly realized, they are expected to increase religious knowledge and instill good behavior for the younger generation and can be applied in a family, school and community environment.